India in the mirror of foreign diplomatic archieves - Zins, Max Jean 1947-; Boquérat, Gilles; France. Ambassade (India). Centre for Human Sciences (New Delhi Manohar Centre de Sciences Humaines, 2004)
On the foreign policies of United States of America and few other Developed countries of the world towards India; contributed articles presented earlier at a seminar.
France's political interaction with India through the Quai d'Orsay archives (1947-1972) / Gilles Boquérat -- America meets India: Jawaharlal Nehru through the eyes of US officials / Dennis Kux -- The Soviet perception of India's foreign policy in the 1940s-1950s / Sergey Lounev -- Cold war in in South Asia: a look at the British archives on India, 1947-1971 / Max-Jean Zins -- The Chinese factor in the American policy towards India: some clues from the US archives / Max-Jean Zins.
Includes bibliographical references.
Keywords: Archives -- Access control -- India; Public records -- Access control -- India; India -- Archival resources; India -- Foreign relations -- 1947-1984.; India -- Foreign relations -- 1984-.